Periodic Co/Nb pseudo spin valve for cryogenic memory - Klenov, Nikolay; Khaydukov, Yury; Bakurskiy, Sergey; Morari, Roman; Soloviev, Igor; Boian, Vladimir; Keller, Thomas; Kupriyanov, Mikhail; Sidorenko, Anatoli; Keimer, Bernhard (Beilstein Journal of Nanotechnology, 2019)
We present a study of magnetic structures with controllable effective exchange energy for Josephson switches and memory applications. As a basis for a weak link we propose to use a periodic structure composed of ferromagnetic (F) layers spaced by thin superconductors (s). Our calculations based on the Usadel equations show that switching from parallel (P) to antiparallel (AP) alignment of neighboring F layers can lead to a significant enhancement of the critical current through the junction. To control the magnetic alignment we propose to use a periodic system whose unit cell is a pseudo spin valve of structure F1/s/F2/s where F1 and F2 are two magnetic layers having different coercive fields. In order to check the feasibility of controllable switching between AP and P states through the whole periodic structure, we prepared a superlattice [Co(1.5 nm)/Nb(8 nm)/Co(2.5 nm)/Nb(8 nm)]6 between two superconducting layers of Nb(25 nm). Neutron scattering and magnetometry data showed that parallel and antiparallel alignment can be controlled with a magnetic field of only several tens of Oersted.
Keywords: cryogenic computing; neutron scattering; spin valve; superconducting spintronics

(untitled) - Soloviev, I. I.; Klenov, N. V.; Bakurskiy, S. V.; Kupriyanov, M. Y.; Gudkov, A. L.; Sidorenko, A. S. (Beilstein J. Nanotechnol., 2017)

(untitled) - Schneider, M. L.; Donnelly, C. A.; Russek, S. E. (J. Appl. Phys., 2018)

(untitled) - Soloviev, I. I.; Schegolev, A. E.; Klenov, N. V.; Bakurskiy, S. V.; Kupriyanov, M. Y.; Tereshonok, M. V.; Shadrin, A. V.; Stolyarov, V. S.; Golubov, A. A. (J. Appl. Phys., 2018)

(untitled) - Schegolev, A. E.; Klenov, N. V.; Soloviev, I. I.; Tereshonok, M. V. (Beilstein J. Nanotechnol., 2016)

(untitled) - Ryazanov, V. V.; Bol’ginov, V. V.; Sobanin, D. S.; Vernik, I. V.; Tolpygo, S. K.; Kadin, A. M.; Mukhanov, O. A. (Phys. Procedia, 2012)

(untitled) - Goldobin, E.; Sickinger, H.; Weides, M.; Ruppelt, N.; Kohlstedt, H.; Kleiner, R.; Koelle, D. (Appl. Phys. Lett., 2013)

(untitled) - Baek, B.; Rippard, W. H.; Benz, S. P.; Russek, S. E.; Dresselhaus, P. D. (Nat. Commun., 2014)

(untitled) - Alidoust, M.; Halterman, K. (Phys. Rev. B, 2014)

(untitled) - Golod, T.; Iovan, A.; Krasnov, V. M. (Nat. Commun., 2015)

(untitled) - Bakurskiy, S. V.; Klenov, N. V.; Soloviev, I. I.; Kupriyanov, M. Y.; Golubov, A. A. (Appl. Phys. Lett., 2016)

(untitled) - Shafranjuk, S.; Nevirkovets, I. P.; Mukhanov, O. A.; Ketterson, J. B. (Phys. Rev. Appl., 2016)

(untitled) - Gingrich, E. C.; Niedzielski, B. M.; Glick, J. A.; Wang, Y.; Miller, D. L.; Loloee, R.; Pratt Jr, W. P.; Birge, N. O. (Nat. Phys., 2016)

(untitled) - Nevirkovets, I. P.; Mukhanov, O. A. (Phys. Rev. Appl., 2018)

(untitled) - Lenk, D.; Morari, R.; Zdravkov, V. I.; Ullrich, A.; Khaydukov, Y.; Obermeier, G.; Müller, C.; Sidorenko, A. S.; von Nidda, H.-A. K.; Horn, S.; Tagirov, L. R.; Tidecks, R. (Phys. Rev. B, 2017)

(untitled) - Lenk, D.; Zdravkov, V. I.; Kehrle, J.-M.; Obermeier, G.; Ullrich, A.; Morari, R.; Krug von Nidda, H.-A.; Müller, C.; Kupriyanov, M. Y.; Sidorenko, A. S.; Horn, S.; Deminov, R. G.; et al. (Beilstein J. Nanotechnol., 2016)

(untitled) - Khaydukov, Y. N.; Vasenko, A. S.; Kravtsov, E. A.; Progliado, V. V.; Zhaketov, V. D.; Csik, A.; Nikitenko, Y. V.; Petrenko, A. V.; Keller, T.; Golubov, A. A.; Kupriyanov, M. Y.; Ustinov, V. V.; et al. (Phys. Rev. B, 2018)

(untitled) - Usadel, K. D. (Phys. Rev. Lett., 1970)

(untitled) - Kuprianov, M. Y.; Lukichev, V. (Sov. Phys. - JETP, 1988)

(untitled) - Obi, Y.; Ikebe, M.; Fujishiro, H. (Phys. Rev. Lett., 2005)

(untitled) - Kushnir, V. N.; Prischepa, S. L.; Cirillo, C.; Vecchione, A.; Attanasio, C.; Kupriyanov, M. Y.; Aarts, J. (Phys. Rev. B, 2011)

(untitled) - Bergeret, F. S.; Volkov, A. F.; Efetov, K. B. (Phys. Rev. Lett., 2001)

(untitled) - Fominov, Y. V.; Chtchelkatchev, N. M.; Golubov, A. A. (Phys. Rev. B, 2002)

(untitled) - Blanter, Y. M.; Hekking, F. W. J. (Phys. Rev. B, 2004)

(untitled) - Mel’nikov, A. S.; Samokhvalov, A. V.; Kuznetsova, S. M.; Buzdin, A. I. (Phys. Rev. Lett., 2012)

(untitled) - Bakurskiy, S. V.; Kupriyanov, M. Y.; Baranov, A. A.; Golubov, A. A.; Klenov, N. V.; Soloviev, I. I. (JETP Lett., 2015)

(untitled) - Obi, Y.; Ikebe, M.; Kubo, T.; Fujimori, H. (Phys. C (Amsterdam, Neth.), 1999)

(untitled) - Stamopoulos, D.; Aristomenopoulou, E.; Lagogiannis, A. (Supercond. Sci. Technol., 2014)

(untitled) - Liu, L. Y.; Chacón Hernandez, U. D.; Xing, Y. T.; Suguihiro, N. M.; Haeussler, D.; Baggio-Saitovitch, E.; Jäger, W.; Solórzano, I. G. (J. Magn. Magn. Mater., 2016)

(untitled) - Lee, S. F.; Huang, S. Y.; Kuo, J. H.; Lin, Y. A.; Lin, L. K.; Yao, Y. D. (J. Appl. Phys., 2003)

(untitled) - Robinson, J. W. A.; Piano, S.; Burnell, G.; Bell, C.; Blamire, M. G. (IEEE Trans. Appl. Supercond., 2007)

(untitled) - Zdravkov, V. I.; Kehrle, J.; Obermeier, G.; Gsell, S.; Schreck, M.; Müller, C.; Krug von Nidda, H.-A.; Lindner, J.; Moosburger-Will, J.; Nold, E.; Morari, R.; Ryazanov, V. V.; et al. (Phys. Rev. B, 2010)

(untitled) - Zdravkov, V.; Sidorenko, A.; Obermeier, G.; Gsell, S.; Schreck, M.; Müller, C.; Horn, S.; Tidecks, R.; Tagirov, L. R. (Phys. Rev. Lett., 2006)

(untitled) - Nagy, D. L.; Bottyán, L.; Croonenborghs, B.; Deák, L.; Degroote, B.; Dekoster, J.; Lauter, H. J.; Lauter-Pasyuk, V.; Leupold, O.; Major, M.; Meersschaut, J.; Nikonov, O.; et al. (Phys. Rev. Lett., 2002)

(untitled) - Lauter-Pasyuk, V.; Lauter, H. J.; Toperverg, B. P.; Romashev, L.; Ustinov, V. (Phys. Rev. Lett., 2002)

(untitled) - Langridge, S.; Schmalian, J.; Marrows, C. H.; Dekadjevi, D. T.; Hickey, B. J. (Phys. Rev. Lett., 2000)

(untitled) - Rehm, C.; Nagengast, D.; Klose, F.; Maletta, H.; Weidinger, A. (Europhys. Lett., 1997)

(untitled) - Hjörvarsson, B.; Dura, J. A.; Isberg, P.; Watanabe, T.; Udovic, T. J.; Andersson, G.; Majkrzak, C. F. (Phys. Rev. Lett., 1997)

(untitled) - Fraerman, A. A.; Karetnikova, I. R.; Nefedov, I. M.; Shereshevskii, I. A.; Silaev, M. A. (Phys. Rev. B, 2005)

(untitled) - Khaydukov, Y. N.; Kravtsov, E.; Zhaketov, V.; Progliado, V.; Kim, G.; Nikitenko, Y. V.; Keller, T.; Ustinov, V.; Aksenov, V.; Keimer, B. (arXiv, 2019)

(untitled) - Golubov, A. A.; Kupriyanov, M. Y. (Nat. Mater., 2017)

(untitled) - Zhu, Y.; Pal, A.; Blamire, M. G.; Barber, Z. H. (Nat. Mater., 2017)